Motivasi Kerja ASN pada Pelatihan Teknis Peningkatan Kinerja Staf di Kantor Kemenag Kota Bima (Ditinjau dari Generasi X dan Generasi Y) - Widiastuti, Ni Made (Universitas Pendidikan Ganesha, 2020)
The purpose of this research is to know the working motivation of Generation X and Generation Y in Technical Training to Improve Staff Performance In The Bima City Ministry Of Religion with 63.89 % training material involving computer and internet. The method that was used in this research is descriptive with quantitative approach. The field result are 43% participant are in their 50 s and 83% are Generation X which still in their 40 s. The result shows Generation X has a score of 3,44 of working motivation also catagorized as very high, external working motivation dimension with a score of 3,33 while Generation Y has internal motivation of 3,28 with high interval criteria, external motivation of 3,54 with very high criteria. Overall working motivation of Generation X and Y reached the score of 3,40 with very high interval criteria. Internal working motivation of generation X is higher than generation Y. To achieve the working motivation that was wanted, the authority need to understand the resource which is in generation X the largest population with 83% have high responsibility in doing work but their achievment is still not maximal so it need to increase the knowledge and skill, in the term of IT, have high self improvment but the independencywhen doing their act is not exellent yet so they need support from work mate, leader and assistant. Generation Y need to improve their internal working motivation with giving them responsibility and working target, because this generation have the ability to use IT which is their talent from their born. Self improvment and indepency in doing their work is a foundation from this generation so they need to be given a challange to make more inovation especially in IT. Abstrak: Penelitian ini bertujuan mengetahui motivasi kerja Generasi X dan Generasi Y pada peserta Pelatihan Teknis Peningkatan Kinerja Staf di Kantor Kemenag Kota Bima dengan materi pelatihan 63.89% berkaitan dengan komputer dan internet. Metode yang digunakan adalah deskriptif dengan pendekatan kuantitatif. Temuan di lapangan 43% peserta usia 50 tahun ke atas dan 83% merupakan Generasi X dengan usia 40 tahun ke atas. Hasil penelitian menunjukan Generasi X memiliki motivasi kerja internal skor 3,44 kreteria interval sangat tinggi, dimensi motivasi kerja eksternal dengan skor 3,33 kreteria interval tinggi sedangkan Generasi Y motivasi kerja internal 3,28 dengan kreteria interval tinggi, motivasi kerja eksternal 3,54 kreteria interval sangat tinggi. Secara keseluruhan motivasi kerja Generasi X dan Y mencapai skor 3,40 dengan interval tinggi. Motivasi kerja internal Generasi X lebih tinggi daripada Generasi Y, sedangkan motivasi kerja eksternal Generasi Y lebih tinggi daripada Generasi X. Pimpinan/pihak yang berwenang untuk mencapai kinerja yang diharapkan agar memahami kondisi SDM yang ada yaitu pada populasi Generasi X adalah populasi terbesar yaitu 83% memiliki tanggungjawab dalam melakukan kerja sangat tinggi namun prestasinya belum maksimal sehingga perlu tambahan pengetahuan dan ketrampilan, dalam hal IT, memiliki pengembangan diri sangat tinggi namun kemandirian dalam bertindak belum memadai sehingga perlu dukungan dan arahan dari rekan kerja, pimpinan serta pemberian sarana yang memadai. Generasi Y ditingkatkan motivasi kerja internalnya dengan cara pemberian tanggung jawab dan target kinerja, karena generasi ini memiliki kemampuan dan ketrampilan IT sebagai bakat dari kelahirannya. Pengembangan diri dan kemandirian dalam bertindak merupakan modal dari generasi ini sehingga perlu diberikan tantangan untuk lebih berinovasi terutama dalam hal IT.